Analisis Pengaruh Pengeluaran Pemerintah, Konsumsi Rumah Tangga dan Net-Ekspor Terhadap Pertumbuhan Ekonomi - Halil Haqizul Putra (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
The purpose of the study was to determine the effect of government spending, household consumption, and net-exports on economic growth in the province of West Nusa Tenggara. The research methodology used panel data regression. From the research results, the results of this study conclude that simultaneously the variables of government expenditure, household consumption and net-exports affect economic growth with the F statistic which is greater than the F table. while the results of the partial test show that the variable government expenditure has no significant effect, while household consumption and net-exports have a significant effect on economic growth.